Observation of a dodecagonal oxide quasicrystal and its complex approximant in the SrTiO3-Pt(1 1 1) system. (23rd February 2017) - Schenk, Sebastian; Förster, Stefan; Meinel, Klaus; Hammer, René; Leibundgut, Bettina; Paleschke, Maximilian; Pantzer, Jonas; Dresler, Christoph; Schumann, Florian O; Widdra, Wolf
Abstract: We report on the formation of a SrTiO3 -derived dodecagonal oxide quasicrystal (OQC) at the interface to Pt(1 1 1). This is the second observation of a two-dimensional quasicrystal in the class of oxides. The SrTiO3 -derived OQC exhibits strong similarities to the BaTiO3 -derived OQC with respect to the local tiling geometry. However, the characteristic length scale of the SrTiO3 -derived OQC is 1.8% smaller. Coexisting with the OQC a large scale approximant structure with a monoclinic unit cell is identified. It demonstrates the extraordinary level of complexity that oxide approximant structures can reach.